THE EFFECT OF WORK DISCIPLINE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT PT. PLN (PERSERO) MAIN DISTRIBUTION UNIT MAKASSAR CITY - Ain, Fara; Budiyanti, Hety; Hamka, Rezky Amalia (Universitas Negeri Makassar, 2025)
Abstract: This study aims to determine the effect of work discipline and work motivation on employee performance at PT. PLN (Persero) Distribution Unit Sulselrabar Makassar City. This type of research, the population is 120 employees with a sample determination of 120 employees. Data collection techniques are carried out by distributing questionnaires. The data analysis technique used is multiple linear regression analysis using Statistical Product Service Solution (SPSS) version 26. The results of the study indicate that partially there is a positive and significant effect of work discipline and work motivation on employee performance at PT. PLN (Persero) Distribution Unit Sulselrabar Makassar City. Then simultaneously there is a significant effect of work discipline and work motivation on employee performance at PT. PLN (Persero) Distribution Unit Sulselrabar Makassar City.Keywords: Work Discipline, Work Motivation, and Employee Performance